Improving Halal Literacy to Encourage Interest in Purchasing Sunscreen with Halal Logo - Kinanti Iraza; Sofiya Azzara Rafles; Sri Ramadhani; Annio Indah Lestari Nasution (Proceeding International Conference on Islamic Economics Community Services (ICIECS), 2023)
This paper investigates the impact of halal literacy on consumer interest in purchasing halal-labeled sunscreen products in Medan. Utilizing data from 250 potential consumers and 15 business respondents, the study employed deep interviews and training sessions to assess how increased halal literacy influences consumer behavior. The findings reveal that consumers with a better understanding of halal principles exhibit a heightened interest in buying sunscreen with a halal logo, driven by perceived quality and religious compliance. The research highlights that while the halal logo alone may not suffice to boost consumer confidence, improved halal literacy significantly enhances trust and purchasing intentions. This increased literacy not only fosters consumer loyalty but also supports business sustainability by reinforcing the market position of halal products. The study concludes that ongoing education on halal standards is essential for manufacturers to effectively attract and retain consumers, emphasizing the need for clear communication about the benefits of halal certification. The implications suggest that businesses should invest in educational campaigns to bridge information gaps and leverage halal literacy to drive product sales.